Kinematic design of a non-parasitic 2R1T parallel mechanism with remote center of motion to be used in minimally invasive surgery applications. (November 2020) - Yaşır, Abdullah; Kiper, Gökhan; Dede, M.İ. Can
Highlights: A novel parallel mechanism for minimally invasive surgery applications is presented. The mechanism has 3-degrees-of-freedom (two rotations, one translation). The mechanism has a remote center of motion. The direct and inverse kinematic model of the mechanism is presented. Dimensional design of the mechanism is perforemed for a desired workspace. Abstract: In minimally invasive surgery applications, the use of robotic manipulators is becoming more and more common to enhance the precision of the operations and post-operative processes. Such operations are often performed through an incision port (a pivot point) on the patient's body. Since the end-effector (the handled surgical tool) move about the pivot point, the manipulator has to move about a remote center of motion. In this study, a 3-degrees-of-freedom parallel mechanism with 2R1T (R: rotation, T: translation) remote center of motion capability is presented for minimally invasive surgery applications. First, its kinematic structure is introduced. Then, its kinematic analysis is carried out by using a simplified kinematic model which consists of three intersecting planes. Then the dimensional design is done for the desired workspace and a simulation test is carried out to verify the kinematic formulations. Finally, the prototype of the final design is presented.